Sex and height determination by foramen magnum morphometry using multiplanar reconstruction (MPR) CT skull images - Annuar, Suraya Hanim Mohamed (2016)
Introduction: Radiological forensic is a specialised area of medical imaging using radiological technique for identification of human and also for ante or post mortem purposes. Radiological imaging of human remains become important in forensic field in determining sex, age, ethnicity, stature and in fact, cause of death. Objective: The aim of this study is to determine the relationship between sex and height with foramen magnum (FM) morphology using multiplanar reconstruction (MPR) computed tomography (CT) scan of the skull. Material and Method: Total of 104 CT scan of the skull were selected using randomised sampling, i.e. 52 samples for each gender. Images were analysed using PACS viewing application on grey-scale monitor. Seven variables of FM morphology were measured on MPR skull images. Comparison between FM morphology and sex, and correlation with height were analysed using statistical test. Results: There is statistically significant difference between males and females for all measurements, with p value < 0.05. The males have larger value than female, in all FM measurements. However, fair degree of correlation between FM parameters and height (0.257<r<0.495; P<0.05) was observed in this study.Conclusion: FM measurements are very useful in studying sexual dimorphism in forensic investigations, but less helpful to determine height of an individu.